A comprehensibility study of pictogram elements for manufacturing steps. (18th December 2009) - Yamazaki, Atsuko K.; Taki, Hirokazu
The authors investigated the effectiveness of pictograms in manufacturing settings, where supervisors and workers often do not share the same language or cultural background. Pictograms for manufacturing steps, such as 'cut', 'push' and 'measure', were designed. Their comprehensibility was examined by questionnaires and a comprehension experiment. The questionnaires were presented to 73 Japanese and 34 Portuguese-speaking subjects. The experiment was conducted with Japanese subjects and each subject's response time to the pictograms was measured. The pictograms for procedures performed by a body part induced erroneous responses when they did not include the object of an intended action. On the other hand, the pictograms for procedures using a tool, such as cutting and measuring, tended to be comprehended more correctly and spontaneously. The results indicate that well-designed pictograms for an action combined with the illustration of an object can be used effectively in manufacturing settings, where safety and productivity are critical.